Negative electrode protection material, secondary battery and electric device

By applying a new protective material composed of silsesquioxane, linear polymer, Upy and cyclic molecular groups on the surface of the lithium metal negative electrode, the problems of lithium dendrites and the cracking of the protective layer are solved, and higher cyclic stability and safety are achieved.

CN119708497APending Publication Date: 2025-03-28SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411880496.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing lithium metal negative electrode surface protective layer is difficult to suppress the growth of lithium dendrites during the circulation process, and it is unable to adapt to the cracking of the protective layer due to changes in the negative electrode surface volume, which poses a risk of battery short circuit and safety.

Method used

A new negative electrode protection material, including silsesquioxane groups, linear polymer groups, Upy groups and cyclic molecular groups, is adopted to form a three-dimensional supramolecular hybrid network through the combination of these groups to provide strength and adaptability to avoid cracking of the protective layer.

Benefits of technology

Effectively inhibit the growth of lithium dendrites, reduce lithium dendrites deposition, provide a fast transmission channel for lithium ions, reduce interface transmission impedance, improve cycle stability, and enhance the strength and durability of the protective layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708497A_ABST
    Figure CN119708497A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode protection material, a secondary battery and an electric device, and relates to the technical field of batteries. The novel negative electrode protection material is applied to a protection layer, a POSS group can provide a rapid transmission channel for lithium ions, and interface transmission impedance is reduced; the linear polymer group can provide a basic cross-linked network for the protective layer; the ureido pyrimidone (UPy) group can provide abundant reversible supramolecular cross-linking points by forming hydrogen bonds, so that a three-dimensional supramolecular hybrid network is formed, and the protective layer has higher strength; the annular molecular group can adapt to volume change in the deposition process of the lithium negative electrode, and side reaction of the lithium negative electrode and electrolyte caused by fracture of the protective layer is avoided. The negative electrode protection material provided by the invention can inhibit the growth of lithium dendrites, reduce the deposition of the lithium dendrites, provide a rapid transmission channel for lithium ions, reduce the interface transmission impedance and effectively improve the cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, in particular to a negative electrode protection material, a secondary battery and an electric device. Background Art

[0002] Lithium-ion batteries are widely used in the field of consumer electronics. However, with the rapid development of electric vehicles and mobile electronic devices, people have higher and higher requirements for battery energy density, safety, cycle performance, etc. Lithium metal is the metal with the smallest relative atomic mass (6.94) and the lowest standard electrode potential (-3.045V) among all metal elements, and its theoretical gram capacity can reach 3860mAh / g. Therefore, using lithium metal as the negative electrode of the battery, combined with some high energy density positive electrode materials, can greatly improve the energy density of the battery (>400Wh / kg) and the operating voltage of the battery (>4.5V). When lithium metal is used as the negative electrode, due to various factors, the electron density may be uneven on the surface of lithium metal, and then tree-like and mossy lithium dendrites are formed on the electrode surface. These lithium dendrites will lead to the degradation of battery performance, and in severe cases, damage to the diaphragm and short circuit of the battery. As a result, the temperature inside the battery rises, which poses a risk of battery explosion and fire.

[0003] In order to solve these problems, a lot of research has been conducted on artificial protective layers on the surface of lithium metal anodes. However, the conventional protective layer is not effective in inhibiting lithium dendrites during the cycle, and during the cycle, the protective layer is difficult to adapt to the volume change of the anode surface and breaks.

[0004] Therefore, developing a new type of lithium negative electrode protection material has become a technical problem that needs to be urgently solved by technicians in this field. Summary of the invention

[0005] Based on this, the purpose of this application is to overcome the shortcomings of the above-mentioned prior art and provide a negative electrode protection material, a secondary battery and an electrical device. The negative electrode protection material can inhibit the growth of lithium dendrites, reduce the deposition of lithium dendrites, provide a fast transmission channel for lithium ions, reduce the interface transmission impedance, and effectively improve the cycle stability.

[0006] To achieve the above-mentioned purpose, in the first aspect of the present application, the technical solution adopted by the present application is: a negative electrode protective material, including silsesquioxane groups, linear polymer groups, Upy groups, and cyclic molecular groups;

[0007] The structural formula of the silsesquioxane group is as shown in formula (I), 8≤Si atom number≤14 and the Si atom number is an even number, R 1is at least one of H, halogen, C1-C10 saturated or unsaturated branched alkyl, C1-C10 straight-chain alkyl, and phenyl-containing aromatic group;

[0008]

[0009] The structural formula of the linear polymer group is shown in formula (II);

[0010]

[0011] 6≤n1≤20, R 2 is at least one of H, halogen, C1-C3 saturated or unsaturated branched alkyl, and C1-C3 straight chain alkyl;

[0012] The structural formula of the Upy group is shown in formula (III), R 3 is at least one of H, halogen, C1-C3 saturated or unsaturated branched alkyl, and C1-C3 straight chain alkyl;

[0013]

[0014] The structural formula of the cyclic molecular group is as shown in formula (IV), 4≤O atoms≤10;

[0015]

[0016] As an embodiment of the present application, in the structural formula (I) of the silsesquioxane group, 10≤the number of Si atoms≤12 and the number of Si atoms is an even number; and / or, in the structural formula (II) of the linear polymer group, 10≤n1≤12; and / or, in the structural formula (IV) of the cyclic molecule group, 8≤the number of O atoms≤10.

[0017] As an embodiment of the present application, in the structural formula (I) of the silsesquioxane group, R 1 is at least one of F, Cl, Br, benzene ring, and vinyl; and / or, in the structural formula (II) of the linear polymer group, R 2 is at least one of F, Cl, Br, benzene ring, and vinyl; and / or, in the structural formula (III) of the Upy group, R 3 It is at least one of F, Cl, Br, benzene ring and vinyl.

[0018] As an embodiment of the present application, the molar ratio of the silsesquioxane group, the linear polymer group, the Upy group, and the cyclic molecular group is silsesquioxane group: linear polymer group: Upy group: cyclic molecular group = 1:1:(5-15):1.

[0019] As an embodiment of the present application, the molar ratio of the silsesquioxane group, the linear polymer group, the Upy group, and the cyclic molecular group is silsesquioxane group: linear polymer group: Upy group: cyclic molecular group = 1:1:(10-12):1.

[0020] As an implementation scheme of the present application, the present application provides a method for preparing the negative electrode protective material, dissolving a compound containing a linear polymer group and a cyclic molecular group in an organic solvent to obtain a mixture A, and stirring; dissolving a compound containing a silsesquioxane group and an Upy group in the mixture A, and stirring; adding an initiator and stirring at room temperature to uniformly dissolve to obtain a precursor solution, namely, the negative electrode protective material.

[0021] As an embodiment of the present application, the organic solvent is tetrahydrofuran (THF), and the initiator is dimethyl benzoate (DMPA).

[0022] In the second aspect of the present application, the present application also provides a negative electrode plate, which includes a negative electrode collector and a negative electrode active material layer and a protective layer sequentially arranged on at least one surface of the negative electrode collector; the protective layer includes the negative electrode protective material.

[0023] As an embodiment of the present application, the thickness of the protective layer is 2-4 μm.

[0024] As an embodiment of the present application, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of graphite, a silicon-oxygen composite material, and a silicon-carbon composite material.

[0025] In a third aspect of the present application, the present application further provides a secondary battery, wherein the secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet mentioned above.

[0026] As an embodiment of the present application, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes at least one of a nickel-cobalt-manganese ternary material, a nickel-aluminum-manganese ternary material, a lithium cobalt oxide material, a lithium iron phosphate material, a lithium manganese oxide material, a lithium iron manganese phosphate material and a nickel manganese spinel material; and / or, the material of the diaphragm is at least one of polypropylene and polyethylene; and / or, the electrolyte is a carbonate electrolyte.

[0027] In a fourth aspect of the present application, the present application provides an electrical device, wherein the electrical device comprises the secondary battery.

[0028] Compared with the prior art, the beneficial effects of the present application are as follows: the present application proposes a novel negative electrode protection material for application in the protective layer, wherein the silsesquioxane (POSS) group can provide a fast transmission channel for lithium ions and reduce the interface transmission impedance; the linear polymer group can provide a basic cross-linking network for the protective layer; the ureidopyrimidone (UPy) group can provide abundant reversible supramolecular cross-linking points by forming hydrogen bonds, thereby forming a three-dimensional supramolecular hybrid network, so that the protective layer has a higher strength; the cyclic molecular group can adapt to the volume change during the lithium negative electrode deposition process, and avoid the rupture of the protective layer, which leads to side reactions between the lithium negative electrode and the electrolyte. The negative electrode protection material provided by the present application can inhibit the growth of lithium dendrites, reduce the deposition of lithium dendrites, provide a fast transmission channel for lithium ions, reduce the interface transmission impedance, and effectively improve the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the infrared spectrum of the negative electrode protection material prepared in Example 1;

[0030] Figure 2 The XRD pattern of the negative electrode protective material prepared in Example 1;

[0031] Figure 3 This is a SEM image of the negative electrode active material layer prepared in Example 1. DETAILED DESCRIPTION

[0032] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with the accompanying drawings and specific embodiments. Its purpose is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application. Unless otherwise specified, the experimental reagents and instruments designed for the implementation and comparative examples of this application are all commonly used ordinary reagents and instruments, which can be obtained from commercial channels. In the implementation and comparative examples, the experimental methods used are all conventional methods unless otherwise specified; and unless otherwise specified, the raw materials used in parallel experiments are from the same batch of raw materials.

[0033] A negative electrode protective material, comprising a silsesquioxane group, a linear polymer group, an Upy group, and a cyclic molecular group;

[0034] The structural formula of the silsesquioxane group is as shown in formula (I), 8≤Si atom number≤14 and the Si atom number is an even number, R 1 is at least one of H, halogen, C1-C10 saturated or unsaturated branched alkyl, C1-C10 straight-chain alkyl, and phenyl-containing aromatic group;

[0035]

[0036] The structural formula of the linear polymer group is shown in formula (II);

[0037]

[0038] 6≤n1≤20, R 2 is at least one of H, halogen, C1-C3 saturated or unsaturated branched alkyl, and C1-C3 straight chain alkyl;

[0039] The structural formula of the Upy group is shown in formula (III), R 3 is at least one of H, halogen, C1-C3 saturated or unsaturated branched alkyl, and C1-C3 straight chain alkyl;

[0040]

[0041] The structural formula of the cyclic molecular group is as shown in formula (IV), 4≤O atoms≤10;

[0042]

[0043] The present application proposes a novel negative electrode protection material for use in a protective layer, wherein the silsesquioxane (POSS) group can provide a fast transmission channel for lithium ions and reduce the interface transmission impedance; the linear polymer group can provide a basic cross-linking network for the protective layer; the ureidopyrimidone (UPy) group can provide abundant reversible supramolecular cross-linking points by forming hydrogen bonds, thereby forming a three-dimensional supramolecular hybrid network, so that the protective layer has higher strength; the cyclic molecular group can adapt to the volume change during the lithium negative electrode deposition process, avoiding the rupture of the protective layer and causing side reactions between the lithium negative electrode and the electrolyte.

[0044] In a specific embodiment of the present application, in the structural formula (I) of the silsesquioxane group, 10≤the number of Si atoms≤12 and the number of Si atoms is an even number; and / or, in the structural formula (II) of the linear polymer group, 10≤n1≤12; and / or, in the structural formula (IV) of the cyclic molecule group, 8≤the number of O atoms≤10.

[0045] In one embodiment, in the structural formula (I) of the silsesquioxane group, the number of Si atoms can be 8, 10, 12 or 14; and / or, in the structural formula (II) of the linear polymer group, n1 can be 6, 7, 9, 10, 11, 12, 13, 14, 16, 18, 20 or a range consisting of any two of the values ​​therein; and / or, in the structural formula (IV) of the cyclic molecular group, the number of O atoms can be 4, 5, 6, 8, 9, 10 or a range consisting of any two of the values ​​therein.

[0046] The inventors found in actual research that the structural formula of the silsesquioxane group will affect the performance of the negative electrode protection material. When the number of Si atoms in the structural formula of the silsesquioxane group is less than 8, the gap in the middle of the cage structure is small and the ion transmission is not good; when the number of Si atoms is greater than 14, the gap in the middle of the cage structure is too large, the stability of the cage structure is insufficient, and the overall strength of the protective layer is poor. The structural formula of the linear polymer group will affect the performance of the negative electrode protection material. n1 is the polymer chain length. When n1 is less than 6, the cross-linked network segment formed has poor mobility and insufficient toughness. When n1 is greater than 20, the cross-linked network formed is too loose and has poor strength. The structural formula of the cyclic molecule group will affect the performance of the negative electrode protection material. When the number of O atoms is small, the diameter of the cyclic molecule is small and cannot enclose the chain molecule. When the number of O atoms is large, the cyclic molecule cannot play the role of converging the chain molecule, inhibiting the self-repair function of the negative electrode protection material.

[0047] In a specific embodiment of the present application, in the structural formula (I) of the silsesquioxane group, R 1 is at least one of F, Cl, Br, benzene ring, and vinyl; and / or, in the structural formula (II) of the linear polymer group, R 2 is at least one of F, Cl, Br, benzene ring, and vinyl; and / or, in the structural formula (III) of the Upy group, R 3 It is at least one of F, Cl, Br, benzene ring and vinyl.

[0048] The inventors found in actual research that the use of halogens and macromolecules grafted at both ends of the polymer chain can further reduce the crystallinity of the polymer, reduce the battery interface impedance, improve the mobility of the polymer protective layer chain segments, improve toughness, and extend the battery cycle performance.

[0049] As an embodiment of the present application, the molar ratio of the silsesquioxane group, the linear polymer group, the Upy group, and the cyclic molecular group is silsesquioxane group: linear polymer group: Upy group: cyclic molecular group = 1:1:(5-15):1.

[0050] As an embodiment of the present application, the molar ratio of the silsesquioxane group, the linear polymer group, the Upy group, and the cyclic molecular group is silsesquioxane group: linear polymer group: Upy group: cyclic molecular group = 1:1:(10-12):1.

[0051] As an implementation scheme of the present application, the present application provides a method for preparing the negative electrode protective material, dissolving a compound containing a linear polymer group and a cyclic molecular group in an organic solvent to obtain a mixture A, and stirring; dissolving a compound containing a silsesquioxane group and an Upy group in the mixture A, and stirring; adding an initiator and stirring at room temperature to uniformly dissolve to obtain a precursor solution, namely, the negative electrode protective material.

[0052] As an embodiment of the present application, the organic solvent is tetrahydrofuran (THF), and the initiator is dimethyl benzoate (DMPA).

[0053] One embodiment of the present application further provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode active material layer and a protective layer sequentially arranged on at least one surface of the negative electrode current collector; the protective layer includes the negative electrode protective material.

[0054] The negative electrode protection material provided in the present application, which includes silsesquioxane groups, linear polymer groups, Upy groups, and cyclic molecular groups, is applied to the protective layer, which can significantly improve the interface stability of the metal lithium negative electrode side, inhibit the growth of lithium dendrites, and reduce lithium dendrite deposition, thereby improving the utilization rate and cycle life of the battery.

[0055] In a specific embodiment of the present application, the thickness of the protective layer is 2-4 μm.

[0056] In one embodiment, the thickness of the protective layer is 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or a range consisting of any two of these values.

[0057] In a specific embodiment of the present application, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of graphite, a silicon-oxygen composite material, and a silicon-carbon composite material.

[0058] An embodiment of the present application further provides a secondary battery, the secondary battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, and the negative electrode sheet is the negative electrode sheet mentioned above.

[0059] In a specific embodiment of the present application, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes at least one of a nickel-cobalt-manganese ternary material, a nickel-aluminum-manganese ternary material, a lithium cobalt oxide material, a lithium iron phosphate material, a lithium manganese oxide material, a lithium iron manganese phosphate material and a nickel manganese spinel material; and / or the material of the diaphragm is at least one of polypropylene and polyethylene; and / or the electrolyte is a carbonate electrolyte.

[0060] In the secondary battery of the present invention, the active materials on the positive and negative electrodes can be matched with different types according to needs, and both can achieve good electrochemical activity and safety and stability.

[0061] An embodiment of the present application further provides an electric device, wherein the electric device comprises the secondary battery.

[0062] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0063] The present application is further described below with specific embodiments:

[0064] Example 1

[0065] A negative electrode protective material, comprising a silsesquioxane group, a linear polymer group, an Upy group, and a cyclic molecular group;

[0066] The structural formula of the silsesquioxane group is shown in formula (V), wherein the number of Si atoms is 8, R 1 is F;

[0067]

[0068] The structural formula of the linear polymer group is shown in formula (VI), n1=10, R 2 is F;

[0069]

[0070] The structural formula of the Upy group is shown in formula (VII), R 3 is F;

[0071]

[0072] The structural formula of the cyclic molecular group is shown in formula (VIII), and the number of O atoms = 8;

[0073]

[0074] The method for preparing the negative electrode protective material comprises the following steps:

[0075] Fluorinated polydecanediol (n1 = 10 straight chain molecules, HO (CF 2 CF 2 ) 10OH) and 24-crown-8 (cyclic molecule with 8 oxygen atoms) were dissolved in tetrahydrofuran (THF) and stirred continuously for 2 hours. Octaperfluorosilsesquioxane and fluoro-2-ureido-4[1H]-pyrimidinone (UPy) were dissolved in THF solution, and then the initiator dimethyl benzoate (DMPA) was added. Stirring was performed at room temperature until all the components were dissolved evenly to obtain a precursor solution.

[0076] The preparation of the secondary battery comprises the following steps:

[0077] Preparation of negative electrode sheet: Roll lithium metal (negative electrode active material layer) on copper foil (current collector) to prepare lithium metal negative electrode, and apply the above precursor solution on the metal lithium negative electrode to control the thickness of the protective layer to 2μm. Irradiate with ultraviolet light for 5 minutes. Then vacuum dry at room temperature for 24 hours to obtain the modified metal lithium negative electrode.

[0078] Preparation of positive electrode sheet: The ternary positive electrode material, binder PVDF and acetylene black are mixed in a mass ratio of 97.5:1:1.5, and then dissolved in N-methylpyrrolidone (NMP) solvent to form a uniform slurry, which is then coated on aluminum foil and baked at 90-120°C, and then rolled and die-cut to obtain the positive electrode sheet.

[0079] Preparation of electrolyte: Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:1:1, and then 10% by mass of fluoroethylene carbonate (FEC) was added to obtain a mixed solvent. Then, 1M lithium hexafluorophosphate (LiPF 6 ) was added into the solvent and stirred at room temperature for 12 h to obtain the electrolyte.

[0080] Preparation of the battery: Polyethylene (PE) with a thickness of 9 μm is selected as the separator, and a Z-shaped stacking method is adopted. The positive electrode and the negative electrode are on both sides of the separator, and the separator is between the electrodes. After stacking, the pole ears are welded. After welding, they are placed in an aluminum-plastic film, and after top and side sealing, liquid injection, and packaging, a lithium metal stacked battery is finally obtained.

[0081] The infrared spectrum of the negative electrode protective material prepared in Example 1 is as follows: Figure 1 As shown, the XRD pattern of the negative electrode protection material prepared in Example 1 is as follows Figure 2 As shown, the SEM image of the negative electrode active material layer prepared in Example 1 is as follows Figure 3 shown. Figure 1 The characteristic peak 779 corresponds to the linear polymer group and the cyclic molecular group -CH 2-group characteristic peak, 1114 is the characteristic peak of Si-O-Si in silsesquioxane group, 1608 is the characteristic peak of CO in linear polymer group and cyclic molecular group, 1409 and 1276 correspond to the characteristic peaks of NH and C=C in Upy group. Figure 2 The X-ray diffraction peaks corresponding to the silsesquioxane group, the cyclic molecular group, and the linear polymer group, respectively, Figure 3 SEM image of the negative electrode active material layer shows that the surface morphology is dense and uniform overall.

[0082] Example 2-6, Comparative Example 1-2

[0083] The difference from Example 1 is that the structural formula of the silsesquioxane group is different, and the others are the same. The silsesquioxane group used in Example 2 is decaprolactone; the silsesquioxane group used in Example 3 is dodecaprolactone; the silsesquioxane group used in Example 4 is tetradecaprolactone; the silsesquioxane group used in Example 5 is octacaprolactone; and the silsesquioxane group used in Example 6 is octaphenylsilsesquioxane. The silsesquioxane group used in Comparative Example 1 is hexacaprolactone; and the silsesquioxane group used in Comparative Example 2 is hexadecaprolactone.

[0084] Examples 7-11, Comparative Examples 3-4

[0085] The difference from Example 1 is that the structural formula of the linear polymer group is different, and the others are the same. The linear polymer group used in Example 7 is perfluoropolydodecanediol; the linear polymer group used in Example 8 is perfluoropolyhexanediol; the linear polymer group used in Example 9 is perfluoropolyeicosandiol; the linear polymer group used in Example 10 is perphenylene polyethylene glycol; the linear polymer group used in Example 11 is polyeicosandiol. The linear polymer group used in Comparative Example 3 is perfluoropolypentanediol; the linear polymer group used in Comparative Example 4 is perfluoropolyhexanediol.

[0086] Examples 12-13

[0087] The difference from Example 1 is that the structural formula of the Upy group is different, and the others are the same. The Upy group used in Example 12 is phenyl 2-ureido-4[1H]-pyrimidone; the Upy group used in Example 13 is 2-ureido-4[1H]-pyrimidone.

[0088] Examples 14-15, Comparative Examples 5-6

[0089] The difference from Example 1 is that the structural formula of the cyclic molecular group is different, and the others are the same. The cyclic molecular group used in Example 14 is 12-crown-4; the cyclic molecular group used in Example 15 is 30-crown-10; the cyclic molecular group used in Comparative Example 5 is 9-crown-3; and the cyclic molecular group used in Comparative Example 6 is 36-crown-12.

[0090] Examples 16-20

[0091] The difference from Example 1 is that the molar ratios of the silsesquioxane group, the linear polymer group, the Upy group and the cyclic molecular group are different, and the others are the same.

[0092] Embodiment 21

[0093] The difference from Example 1 is that the thickness of the protective layer is different, and the others are the same.

[0094] Comparative Example 7

[0095] The difference from Example 1 is that no silsesquioxane group is contained, and the other aspects are the same.

[0096] Comparative Example 8

[0097] The difference from Example 1 is that the Upy group is not contained, and the other aspects are the same.

[0098] Comparative Example 9

[0099] The difference from Example 1 is that there is no cyclic molecular group, and the other aspects are the same.

[0100] The preparation methods of the embodiments and comparative examples refer to those of Example 1, and the differences are shown in Table 1.

[0101] Table 1

[0102]

[0103]

[0104]

[0105]

[0106] Performance test: The assembled battery is tested and characterized for electrochemical cycle performance using the Xinwei test system. The charge and discharge rate is set to 1C, the charge and discharge voltage range is 2.8-4.25V, and the temperature is kept constant at 25°C during the test. The battery cycle performance is evaluated by the number of cycles when the battery capacity decays to 80%.

[0107] Protective layer interface impedance / Ω: The assembled battery was measured for impedance using a CHI660 electrochemical workstation with a frequency of 0.1-100000HZ, and the interface impedance was then obtained by fitting the test curve using the Zview software.

[0108] Elastic modulus of protective layer / MPa: The protective layer is coated on the surface of the lithium strip and tested by a Young's modulus tester;

[0109] Strength of protective layer / Mpa: The protective layer is made into a polymer film alone, and the strength of the protective layer is measured by a tensile tester.

[0110] Short circuit rate (%), number of cycles at 80% capacity retention rate: Cycle test is carried out on the battery testing system, the charge and discharge voltage range is 2.8-4.25V, the charge and discharge cycle is carried out at a rate of 1C, and the short circuit rate is whether the battery short-circuit occurs within 3 cycles; the number of cycles at 80% capacity retention rate is the number of cycles during the battery cycle process when the capacity is not less than 80% of the design value.

[0111] The performance test results are shown in Table 2

[0112] Table 2

[0113]

[0114]

[0115]

[0116] From the above results we can see that:

[0117] From the above embodiments and comparative examples, the secondary battery provided by the present scheme can improve the performance of the secondary battery in multiple dimensions such as the short circuit rate, cycle stability, and mechanical property retention of the battery through the selection of specific negative electrode protective materials. The negative electrode protective materials include silsesquioxane groups, linear polymer groups, Upy groups, and cyclic molecular groups.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A negative electrode protective material, characterized in that: Including silsesquioxane groups, linear polymer groups, Upy groups, and cyclic molecular groups; The structural formula of the silsesquioxane group is as shown in formula (I), 8≤Si atoms≤14 and the number of Si atoms is an even number, R 1 is at least one of H, halogen, C1-C10 saturated or unsaturated branched alkyl, C1-C10 straight-chain alkyl, and phenyl-containing aromatic group; The linear polymer group structural formula is shown in formula (II); 6≤n1≤20, R 2 is at least one of H, halogen, C1-C3 saturated or unsaturated branched alkyl, and C1-C3 straight chain alkyl; The Upy group structural formula is shown in formula (III), R 3 is at least one of H, halogen, C1-C3 saturated or unsaturated branched alkyl, and C1-C3 straight chain alkyl; The structural formula of the cyclic molecular group is as shown in formula (IV), 4≤O atoms≤10; 2. The negative electrode protective material according to claim 1, characterized in that In the structural formula (I) of the silsesquioxane group, 10≤the number of Si atoms≤12 and the number of Si atoms is an even number; and / or, in the structural formula (II) of the linear polymer group, 10≤n1≤12; and / or, in the structural formula (IV) of the cyclic molecular group, 8≤the number of O atoms≤10.

3. The negative electrode protective material according to claim 1, characterized in that In the structural formula (I) of the silsesquioxane group, R 1 is at least one of F, Cl, Br, benzene ring, and vinyl; and / or, in the structural formula (II) of the linear polymer group, R 2 is at least one of F, Cl, Br, benzene ring, and vinyl; and / or, in the structural formula (III) of the Upy group, R 3 It is at least one of F, Cl, Br, benzene ring and vinyl.

4. The negative electrode protective material according to claim 1, characterized in that: The molar ratio of the silsesquioxane group, the linear polymer group, the Upy group and the cyclic molecular group is silsesquioxane group: linear polymer group: Upy group: cyclic molecular group = 1:1:(5-15):

1.

5. The negative electrode protective material according to claim 1, characterized in that The molar ratio of the silsesquioxane group, the linear polymer group, the Upy group and the cyclic molecular group is silsesquioxane group: linear polymer group: Upy group: cyclic molecular group = 1:1:(10-12):

1.

6. A negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer and a protective layer sequentially arranged on at least one surface of the negative electrode current collector; the protective layer comprises the negative electrode protective material according to any one of claims 1-5.

7. The negative electrode sheet according to claim 6, characterized in that: The thickness of the protective layer is 2-4 μm.

8. The negative electrode sheet according to claim 6, characterized in that: The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of graphite, a silicon-oxygen composite material, and a silicon-carbon composite material.

9. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, and the negative electrode sheet is the negative electrode sheet according to any one of claims 6 to 8.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.